Calculation of reservoir capacity loss due to sediment deposition in the `Muela reservoir, Northern Lesotho - Khaba, Liphapang; Griffiths, James Andrew (Elsevier, 2017)
Bathymetry survey records of the `Muela Reservoir in northern Lesotho were obtained from the Lesotho Highlands Development Authority (LHDA) with the aim of identifying reservoir storage capacity loss due to sediment deposition, between 1985 and 2015. For this purpose, data from eight surveys completed between 1985 and January 2015 were analyzed to quantify bathymetric change between each survey. Four interpolation methods (inverse distance weighting, Kriging, natural neighbor, and spline), were used to create digital terrain models from each survey data-set. In addition, a triangulated irregular network (TIN) surface was created from each data-set. The average reservoir storage capacity loss of 15,400 m3/year was determined across the whole period between 1985 and early 2015, based on Kriging. Whilst the results indicate high inter-annual variability in the rate of reservoir capacity reduction, consideration of errors in the surveying and reservoir volumetric calculation methods suggest that rates of reservoir volume reduction can vary between 11,400 m3/year and 18,200 m3/year.